Successful Treatment of Immune Checkpoint Inhibitor–Induced Bullous Pemphigoid with Omalizumab: A Case Report and Review of the Literature - Chen J; Xu D; He Z; Ma S; Liu J; Dai X; Luo Y; Ye X (Clinical, Cosmetic and Investigational Dermatology, 2024)
Jiazhen Chen,1,2,* Duanni Xu,1,2,* Zezhi He,1,2 Shaoyin Ma,1,2 Jiahui Liu,1,2 Xiangnong Dai,1,2 Yuwu Luo,1,2 Xingdong Ye1,2 1Department of Dermatology, Guangzhou Dermatology Hospital, Guangzhou, 510095 People’s Republic of China; 2Institute of Dermatology, Guangzhou Medical University, Guangzhou, 510095, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xingdong Ye; Yuwu Luo, Department of Dermatology, Guangzhou Dermatology Hospital, 56 Hengfu Road, Yuexiu District, Guangzhou, Guangdong, 510095, People’s Republic of China, Tel +86 020 83591975, Email yxingdong@qq.com; 1263009@qq.comBackground: Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment by enhancing the immune system’s ability to target cancer cells. However, ICIs can lead to immune-related adverse events (irAEs), including dermatologic manifestations such as bullous pemphigoid (BP).Objective: To evaluate the efficacy and safety of omalizumab and other biologics in the treatment of ICI-induced refractory bullous pemphigoid and to derive a strategy for selecting biologic treatments for this condition.Methods: A 48-year-old female with pulmonary squamous cell carcinoma developed erythema and blisters following tislelizumab treatment. Despite initial steroid therapy (1.8 mg/kg/day), new blisters formed. Laboratory tests revealed elevated BP180/230 levels, confirming BP diagnosis. Treatments with intravenous corticosteroids, cyclosporine, and dapsone were ineffective. Omalizumab 300 mg every four weeks was initiated based on elevated serum IgE levels. The patient’s response was monitored over four weeks. A comprehensive literature review was conducted, including 4 relevant articles.Results: Omalizumab treatment resulted in the cessation of blister formation and significant symptom alleviation within one week. The overall treatment duration was four weeks, with stable improvement observed. Follow-up for 4 months with no recurrence.Conclusion: This case illustrates the challenges of managing ICI-induced BP and highlights omalizumab as a potentially effective treatment option. The study proposes a personalized therapeutic strategy for refractory ICI-induced BP, emphasizing the selection of biologic agents based on specific immune profiles, including serum markers like IgE, eosinophils, and cytokine levels.Keywords: immune checkpoint inhibitors, bullous pemphigoid, omalizumab, adverse events, case report